Supply and Demand for Discrimination: Strategic Revelation of Own Characteristics in a Trust Game - Heyes, Anthony; List, John A. (American Economic Review, 2016)
In strategic settings a player may be able to influence the behavior of an opponent by revealing information about their own characteristics. They may for example aim to exploit stereotypes held by others. We provide an experimental test of this. A substantial fraction of players in a trust game exhibit a positive willingness to pay to reveal a photograph of themselves to their randomly-assigned partner. This suggests that they perceive that they can use their own characteristics to influence the behavior of others. The demand for such self-revelation depends negatively on price.